HERMENEUTIKA AWARENESS IN UNDERSTANDING THE AL-QUR'AN - Abd Muid N; Muhammad Adlan Nawawi (STIT AL-AMIN KREO TANGERANG, 2020)
The relationship between the Qur'an as the object of interpretation and humans as the subject of interpretation is a dynamic relationship. The variety of methods of interpretation and the variety of results of interpretation is evidence of this fact. In fact, if there is uniformity in the method of interpretation and uniformity of the results of interpretation, then there must be something wrong in the relationship between the Qur'an and its interpreters. This conclusion is drawn after examining the relationship between the Qur'an and its interpreters from a phenomenological point of view. Al-Qur'an is a text that lives and interacts with the horizon that surrounds it. Likewise the horizon of readers and interpreters. The existence of the subject as a reader and interpreter produces various ways and outputs of understanding. The subject speaking with the text within the scope of both interacting with each other is a form of phenomenological activity. The subject perceives the text as a sign that points to various realities. In phenomenological study, phenomena are not shrouded by a curtain of reality that results from the perception of the subject. Thus, the meanings of the text are not born in a vacuum, but always involve subject awareness. The consequence of this is that the development of understanding and the development of methodology in understanding the Al-Qur'an (text) is a necessity. Text horizons will always interact with the subject horizon based on the consciousness that has grown over time and epoch.